A Novel Single-Staged Technique for the Treatment of Soft Tissue in an Oblique Facial Cleft. Issue 6 (September 2016) - Ascha, Mona; Harvey, Donald; Becker, Devra; Rowe, David; Sarma, Hiteswar; Lakin, Gregory E.
Abstract : Introduction: Oblique facial clefts are extremely rare and cause significant morbidity. Treatment of these clefts is complex and requires a fundamental understanding of cleft classification and techniques used for treatment of clefts. Methods: We describe a novel single-staged technique to repair the Tessier no. 4 soft tissue cleft and reconstruct the buccal sulcus and bilaminar lower eyelid by preserving normally excised tissue combined with standard procedures. We also present a case report demonstrating the technique in an adolescent female. The procedure incorporates turnover flaps from soft tissue preservation within the cleft, a Mustarde cheek advancement flap, an anatomical subunit lip repair, a dorsal nasal Rieger flap for ala repositioning, and a lateral nasal flag flap. Results: The single-staged soft tissue repair eliminated the Tessier no. 4 cleft while simultaneously reconstructing the bilaminar lower eyelid and buccal lining. Our patient had no complications within the perioperative period. Conclusions: This novel single-staged technique for the treatment of the soft tissue Tessier no. 4 cleft not only repairs the cleft but also reconstructs the buccal sulcus and bilaminar lower eyelid with turnover flaps preserved from the normally discarded excess soft tissue within the cleft. The novel repair allows for the creation of a deeper fornix to aid with placement of an orbital prosthesis and is ideal for use in underserved or remote locations.